Social Economic and Ecological Adaptive Strategy of Livelihood of Smallholders in the Oil Palm Expansion Areas (Case Studies in Two Villages of Central Kalimantan) - Kumala Putri, Eka Intan; Dharmawan, Arya Hadi; Amalia, Rizka; K. Pandjaitan, Nurmala (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTThe impact of oil palm plantation expansion is felt by the farmers’ households in Central Kalimantan, such as income change, new sources of livelihood related to oil palm, and social economy-ecology ecosystem change. For that, there needs to be an ecological socio-economic strategy. The purpose of this research is to know how socio economic-ecological strategy of farmer’s household in facing the impact of oil palm plantation expansion. Focuses on aspects of socio economic-ecological adaptation mechanisms in relation to local income and their implications for poverty alleviation. The method used is in depth interview, survey, observation and Focus Group Discussion. The analysis used in this research is descriptive qualitative-quantitative. The results showed that there are two factors causing conversion of land into palm land that is economic and policy factors. Conversion of land into oil palm in Beringin Agung Village and Pendahara Village was then addressed differently by farmer households through various adaptation strategies. Adaptation strategies carried out by farmers’ households in two research sites include social economic and ecological strategy. All layers of households in Beringin Agung Village tend to have little choice of adaptation strategy because of the large number of land conversion into oil palm plantations. Meanwhile, all layers of farm households in Pendahara Village have relatively varied adaptation strategies because there are still many natural resources around there.Keywords: adaptation, farmers, households, land conversion, livelihood strategies, oil palmABSTRAKDampak ekspansi perkebunan Sawit dirasakan oleh rumahtangga petani di Kalimantan Tengah, berupa perubahan pendapatan, munculnya sumber mata pencaharian baru yang berhubungan dengan Sawit, berubahnya sosial ekonomi dan ekologi ekosistem. Untuk itu, perlu ada strategi sosial ekonomi ekologi. Tujuan penelitian ini adalah untuk mengetahui bagaimana strategi adaptasi sosial ekonomi ekologi rumahtangga petani dalam menghadapi dampak ekspansi perkebunan Sawit, dan berfokus pada aspek mekanisme adaptasi sosial-ekonomi-ekologi dalam kaitannya dengan ekonomi lokal dan implikasinya terhadap penanggulangan kemiskinan. Metode penelitian menggunakan in depth interview, survey, observasi dan Focus Group Discussion (FGD). Analisis yang digunakan adalah deskriptif kualitatif-kuantitatif. Hasil penelitian menunjukan bahwa terdapat dua faktor penyebab konversi lahan menjadi Sawit yaitu faktor ekonomi dan faktor kebijakan. Konversi lahan hutan menjadi Sawit disikapi secara berbeda oleh rumahtangga petani melalui berbagai strategi adaptasi bertahan hidupnya. Strategi adaptasi yang dilakukan oleh rumahtangga petani meliputi strategi ekonomi, sosial dan strategi ekologi. Semua lapisan rumahtangga di Desa Beringin Agung cenderung tidak banyak mempunyai pilihan strategi adaptasi karena telah banyaknya konversi lahan menjadi perkebunan Sawit, sehingga cenderung homogen. Sementara itu, semua lapisan rumahtangga petani di Desa Pendahara relatif heterogen strategi adaptasinya karena masih ketersediaan sumberdaya alam yang melimpah disana.Kata kunci: adaptasi, Kelapa Sawit, konversi lahan, petani, rumahtangga, strategi nafkah